1998
DOI: 10.1093/humrep/13.suppl_4.117
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian markers of implantation potential in assisted reproduction

Abstract: In-vitro fertilization provides evidence for the heterogeneity of human embryos; data from the UK indicating that approximately 90% of embryos selected for transfer fail to implant. The need to identify factors that promote implantation or markers of implantation is self-evident. There is an increasing awareness that the heterogeneity of follicles may have a significant impact on oocyte competence and embryo viability and that factors which contribute to the heterogeneity of follicles may provide markers of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Antral follicles (seen on ultrasound), unlike the preantral and primordial follicles, do not derive their blood flow directly from ovarian stromal vessels but develop, through the process of neovascularization, a vascular sheath consisting of arterioles, venules and capillaries in the surrounding theca layer [7,8]. Although the precise regulation of this cyclic angiogenesis and consequent neovascularization in the human ovary remains unclear, a number of angiogenic factors and inhibitors are likely to be involved including vascular endothelial growth factor (VEGF) [8,10,24]. In addition, a number of IVF studies have shown that each mature follicle has unique blood flow characteristics and perifollicular capillary bed development [4,11,26,27] supporting the concept that not all follicles are 'created equal' in terms of vasculature [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antral follicles (seen on ultrasound), unlike the preantral and primordial follicles, do not derive their blood flow directly from ovarian stromal vessels but develop, through the process of neovascularization, a vascular sheath consisting of arterioles, venules and capillaries in the surrounding theca layer [7,8]. Although the precise regulation of this cyclic angiogenesis and consequent neovascularization in the human ovary remains unclear, a number of angiogenic factors and inhibitors are likely to be involved including vascular endothelial growth factor (VEGF) [8,10,24]. In addition, a number of IVF studies have shown that each mature follicle has unique blood flow characteristics and perifollicular capillary bed development [4,11,26,27] supporting the concept that not all follicles are 'created equal' in terms of vasculature [25].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity for the detection of blood flow was set at 0.09 cm/s for all the cases. During power Doppler ultrasound colour gain for all the cases was set at the level A3 [10], where A stands for amplitude and A3 denotes highest amount of persistence, 10 shows the level of colour gain when the noise (over-gaining) just disappears. All scans were performed by a single operator (SMS) at the same time each morning (between 7 am and 9.30 am), thus controlling the effects of circadian variation on blood flow [20].…”
Section: Power Doppler Ultrasound Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the United Kingdom show that nearly 90% of embryos selected for transfer fail to implant (2). Poor oocyte/embryo quality and the poor endometrial receptivity are suggested to be the major causes of IVF treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian reserve is one of the factors that determine the efficacy of IVF (Gregory, 1998;Navot et al, 1987;Scheffer et al, 2003). Assessing the ovarian reserve, specialists draw conclusions based on the prospects of ovarian stimulation in a particular patient.…”
Section: In Vitro Fertilization and Known Reasons That Reduce Its Effmentioning
confidence: 99%